Nest-site fidelity and cavity reoccupation by Blue-fronted Parrots Amazona aestiva in the dry Chaco of Argentina - Berkunsky, Igor (2009)
The frequency of cavity reoccupation in secondary cavity nesters depends on several factors including quality of cavities, degree of nest-site fidelity, competition with other cavity nesters and availability of new cavities. Blue-fronted Parrots Amazona aestiva are secondary cavity nesters that live in subtropical forests and savannas of central South America. We examined the characteristics of the trees and cavities used by this species in a protected area of the dry Chaco of Argentina and estimated nest-site fidelity and cavity reoccupation. We also assessed whether the probability of cavity reoccupation was associated with cavity characteristics and nesting success during the previous year. Nest-site fidelity of banded females was 68% and cavity reoccupation by banded and unbanded individuals 62%. Probability of reoccupation was associated with wall thickness and depth of the cavity, and was lower if the nest failed the previous year than if it was successful. The high rate of cavity reoccupation in Blue-fronted Parrots is largely attributable to strong nest-site fidelity and may reflect preferences for cavities whose characteristics are associated with higher nesting success. © 2008 The Authors.